Homoerotic sociability and identity relations: the case of journal o snob (Rio de Janeiro, decade of 1960) (Tempo e Argumento, 2010)
This paper studies a  homoerotic sociability network in Rio de Janeiro in the decade of 1960 through  an analysis of reports contained in the journal "O Snob" (1963-1969) produced by a group that formed this network and  that circulated among its participants. This is an investigation of identity  constructions that those characters held in a sociability area segregated by  the larger society but, at the same time, in dialogue with it. Analyzing issues  commented internally by these groups with the backdrop of the prevailing norms  of heterocentric behavior in the period, I identified the existence of original  experiments in search of a "normal homosexual body". Sociosexual  changes promoted by these experiments reflected in their sociability spaces and  in sexual partnerships, facilitating the emergence of new sexual and/or  emotional possibilities. So, I try to demonstrate that the form of integration  undertaken by the study groups was directly linked to an inflexibility of  gender roles of the time, and, over time, it started to detach from this  rigidity in order to built new ways of acting. The study of the peculiar  trajectory of groups that formed the network, linking it to the identity  movements of the time, can contribute to discussions of individual rights  history, specifically the struggle for sexual equality, and the debate over gay  occupying spaces.
Keywords: homosociability; gender identities; segregated spaces; gaypress